Insights of OxyR role in mechanisms of host–pathogen interaction of Corynebacterium diphtheriae - Cappelli, Elisabete Alves; do Espírito Santo Cucinelli, Andrezza; Simpson-Louredo, Liliane; Canellas, Maria Eurydice Freire; Antunes, Camila Azevedo; Burkovski, Andreas; da Silva, Jemima Fuentes Ribeiro; Mattos-Guaraldi, Ana Luíza; Saliba, Alessandra Mattos; dos Santos, Louisy Sanches (Brazilian Journal of Microbiology, 2022)
Corynebacterium diphtheriae, the leading causing agent of diphtheria, has been increasingly related to invasive diseases, including sepsis, endocarditis, pneumonia, and osteomyelitis. Oxidative stress defense is required not only for successful growth and survival under environmental conditions but also in the regulation of virulence mechanisms of human pathogenic species, by promoting mucosal colonization, survival, dissemination, and defense against the innate immune system. OxyR, functioning as a negative and/or positive transcriptional regulator, has been included among the major bacterial coordinators of antioxidant response. OxyR was first reported as a repressor of catalase expression in C. diphtheriae. However, the involvement of OxyR in C. diphtheriae pathogenesis remains unclear. Accordingly, this work aimed to investigate the role of OxyR in mechanisms of host–pathogen interaction of C. diphtheriae through the disruption of the OxyR of the diphtheria toxin (DT)–producing C. diphtheriae CDC-E8392 strain. The effects of OxyR gene disruption were analyzed through interaction assays with human epithelial cell lines (HEp-2 and pneumocytes A549) and by the induction of experimental infections in Caenorhabditis elegans nematodes and Swiss Webster mice. The OxyR disruption exerted influence on NO production and mechanism accountable for the expression of the aggregative-adherence pattern (AA) expressed by CDC-E8392 strain on human epithelial HEp-2 cells. Moreover, invasive potential and intracytoplasmic survival within HEp-2 cells, as well as the arthritogenic potential in mice, were found affected by the OxyR disruption. In conclusion, data suggest that OxyR is implicated in mechanisms of host–pathogen interaction of C. diphtheriae.
CRIS-Team Scopus Importer:2022-02-25
Keywords: C. diphtheriae; C. elegans; Nitrosative stress; Oxidative stress; OxyR; Virulence